Abortion Policy as Structural Sexism: An Analysis of Shame-Inducing Counseling Laws and Birth Outcomes - Zoë Bergman; Patricia Homan; Jessica Sanders; Bethany Everett (Journal of Health and Social Behavior, 2026)
Both pre- and post- Dobbs research has found that policies restricting abortion access are associated with an increased risk of adverse maternal and fetal outcomes. Previous research demonstrates stigma within reproductive health as a fundamental cause of health inequalities. In this study, we differentiate between state-level policies that restrict access to care compared to policies that foster uncertainty, stigmatize, or induce shame among abortion seekers through mandated counseling. Using data from the Pregnancy Risk Assessment Monitoring System survey (2011–2019), we estimate general linear models (N = 307,692) showing that for each additional shame-inducing abortion policy in a state’s mandated counseling laws, birthing people were 3% more likely to have a preterm birth (risk ratio [RR] = 1.03; p < 0.01) and to give birth to a low-birth-weight baby (RR = 1.03; p < 0.001). We argue that the association between shame-inducing policy measures and adverse birth outcomes reflects an understudied feature of structural sexism that shapes reproductive health outcomes.